Gambaran Karakteristik Pasien Hipertensi di Puskesmas Putri Ayu Kota Jambi - Dwi Yunita Rahmadhani; Marnila Yesni (3031-8572, 2025)
Hypertension is a condition where there is an increase in systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg. Hypertension often makes sufferers unaware that they have hypertension because it often appears without symptoms. Therefore, hypertension is often referred to as the silent killer. The Jambi Province Health Profile shows that hypertension is the first of the 10 highest diseases in Jambi Province with a total of 141,723 cases out of 766,264 cases or 18.5%. Age ≥45 years is more likely to suffer from hypertension compared to age ≤45 years. This research is quantitative research. The population in this study was 1,124 hypertension patients. The sample in this study was all hypertensive patients recorded in the medical records of the Putri Ayu Health Center, Jambi City in January-June 2024, totaling 107 patients. The research design used was analytical descriptive by taking secondary data, namely medical records, and using purposive sampling. The research results showed that the majority of respondents were pre-elderly (45-59 years) as many as 61 respondents (57.0%). 78 respondents (72.9%) were female. 44 respondents (16.8%) worked as housewives. 66 respondents (61.7%) had a high school education. 40 respondents (37.4%) had experienced hypertension of short duration 1-5 years. 74 respondents (69.2%) had grade 1 blood pressure 140/90-159/100 mmHg. The conclusion is that the gender of hypertension sufferers shows that the number of female patients is greater than that of male patients, the age of hypertension sufferers is found to be > 45 years or are included in the pre-elderly category, the number of hypertension sufferers is found to be in household work or not working more than other jobs, there are many sufferers. educated at high school level, sufferers experienced more short duration 1-5, more sufferers of degree 1 compared to other degrees.